Measuring the Urgency of Distributive Justice Perspective of Sharia Economic Law - Rani Mariana; Hasan Bisri; Ija Suntana (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2023)
Inequality is a universal problem faced by all modern economic systems. Economic injustice and inequality of income and wealth are the beginning of the problem of poverty. The emergence of the concept of distributive justice in Islamic economics is motivated by the fact that existing economic theories are unable to overcome the problem of poverty and inequality of income and wealth. Therefore, the study of distribution has always been an interesting study in the field of Islamic economics. This paper explains the concept of distribution in the perspective of Islamic economics, analyzes issues of injustice in the Indonesian distribution system, criticizes the distribution of capitalist economics and ends with a study of Islamic economic distribution in realizing distributive justice and distribution mechanisms in Islam as a solution for justice and community welfare.